Clash of the titans (2010) [videorecording (DVD)] - Leterrier, Louis, 1973-; Worthington, Sam, 1976-; Arterton, Gemma; Mikkelsen, Mads, 1965-; Davalos, Alexa; Fiennes, Ralph; Neeson, Liam; Huston, Danny, 1962-; Flemyng, Jason (Warner Home Video, 2010)
When Hades, the god of the underworld, takes his family, Perseus embarks on a mission to defeat him before he can seize ultimate power and unleash hell on earth.